Monseñor Thiel and nature in Costa Rica - Hilje Quirós, Luko (2020)
Received: 03-02-2020 Approved: 03-27-2020 While acting as the bishop of Costa Rica (1880-1901), Bernardo Augusto Thiel, a multifaceted German priest, did not restrict himself solely to his demanding ecclesiastic activities, but also became involved in issues related to ethnography, linguistics, anthropology, history and demography. This paper reveals that he was also interested in biological sciences, as is shown in a myriad of notes regarding flora and fauna, in field accounts written during his evangelization journeys through indigenous territories. In addition, he kept a collection of archaeological objects and birds, including Iridophanes pulcherrimus aureinucha, collected in Ecuador and later described as a new subspecies to science. Finally, he promoted actions for developing a botanical snake antivenom, and vehemently expressed concerns about deforestation that was already taking place in Costa Rica.